2017
DOI: 10.1371/journal.pone.0180610
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional GPR40/FFAR1 signaling exacerbates pain behavior in mice

Abstract: We previously showed that activation of G protein-coupled receptor 40/free fatty acid receptor 1 (GPR40/FFAR1) signaling modulates descending inhibition of pain. In this study, we investigated the involvement of fatty acid-GPR40/FFAR1 signaling in the transition from acute to chronic pain. We used GPR40/FFAR1-knockout (GPR40KO) mice and wild-type (WT) mice. A plantar incision was performed, and mechanical allodynia and thermal hyperalgesia were evaluated with a von Frey filament test and plantar test, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Dragano et al also confirmed FFAR1 is expressed in hypothalamic neurons (both in neuropeptide Y (NPY) and POMC neurons) and acts to maintain whole body energy homeostasis by decreasing energy efficiency and reducing hypothalamic inflammation when FFAR1 is chemically activated by receptor specific agonists (38). Additional studies demonstrate that polyunsaturated fatty acids (PUFAs)-mediate FFAR1 activation in the hypothalamus to produce an anti-inflammatory and neuroprotective effect (37, 4952). This apparent discrepancy in the effects of FFAR1 is most likely attributable to a ligand-dependent activation of distinct allosteric sites on the receptor by the different molecular structures (53).…”
Section: Discussionmentioning
confidence: 99%
“…Dragano et al also confirmed FFAR1 is expressed in hypothalamic neurons (both in neuropeptide Y (NPY) and POMC neurons) and acts to maintain whole body energy homeostasis by decreasing energy efficiency and reducing hypothalamic inflammation when FFAR1 is chemically activated by receptor specific agonists (38). Additional studies demonstrate that polyunsaturated fatty acids (PUFAs)-mediate FFAR1 activation in the hypothalamus to produce an anti-inflammatory and neuroprotective effect (37, 4952). This apparent discrepancy in the effects of FFAR1 is most likely attributable to a ligand-dependent activation of distinct allosteric sites on the receptor by the different molecular structures (53).…”
Section: Discussionmentioning
confidence: 99%
“…GPR40 activation by the synthetic agonist GW9508 ( 36 ) has been associated with synaptic plasticity ( 37 ), a reduction in depressive behavior ( 38 ), and a reduction in pain symptoms and inflammation in mice ( 39 ). Moreover, knock-down experiments demonstrate mice lacking GPR40 protein receptors had higher pain and inflammation ( 40 , 41 ), and mice injected with inflammatory agents increased GPR40 expression compared with a control group ( 39 ). The underlying mechanisms are not well elucidated, but they may involve an upregulation of β-endorphins or regulation of cytokines ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same group of researchers also found that repeating the administration of naloxone exacerbated mechanical allodynia due to postoperative pain. This suggests that the underlying mechanism for pain exacerbation induced by inhibition of the G protein-coupled receptor 40/free fatty acid receptor 1 may be associated with naloxone-induced exacerbation of postoperative pain (Nakamoto et al, 2017). Using a chronic pain mouse model, Wang et al (2017) investigated individual variance in two dimensions of pain behaviors: sensory and emotional.…”
Section: Mouse Models Of Chronic Pain and Stressmentioning
confidence: 99%